Generative AI : unlocking the next chapter in healthcare - Mahajan, Rohit; Uberoy, Ritu M. (Productivity Press, 2026)
From algorithms that draft clinical notes in seconds to autonomous agents that triage emergency room backlogs, artificial intelligence is quietly reshaping every facet of healthcare.
Keywords: Artificial intelligence -- Medical applications.; Generative artificial intelligence.; elektronické knihy; electronic books